Aspectos e fatores da produtividade em pesquisa, desenvolvimento e inovação - Politzer,Kurt (2005)
Comparison of national budgets for R&D is often made but it should consider the relative productivity and their factors. In Brazil, inefficiency factors as well as their causes have been diagnosed since the late 60's and solutions have been proposed within various governmental organisms, from CNPq to the strategy think tanks. Problems that hinder R&D and innovation in Brazil are reviewed from a historical perspective together with the proposed solutions providing a detailed analysis of the difficulties that have to be overcome to achieve a more effective innovation environment, adequate for the present times, challenges and opportunities.